Pengaruh Pengetahuan Pemberian Leaflet Tentang Cara Penggunaan Dan Penyimpanan Obat Tetes Mata Di Apotek Gawok Sukoharjo - Anti Tirani Wahyuning Pertiwi; H Hartono (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Knowledge is the result of someone's sense of knowing that has occurred after someone has sensed a certain object. Sensing occurs through the five senses it has such as eyes, nose, ears which are based on knowledge. In this study also used leaflets to provide explanations. Leaflets are practical and easy to carry anywhere. Leaflets are designed with attractive colors and pictures that attract someone to read the information described in the leaflet. The purpose of this study was to increase patient knowledge about how to use and store eye drops at the Gawok Sukoharjo pharmacy. This study uses cross sectional analytic methods with a one group pre-test podt test design research technique. The results of this study on the pretest questionnaire were that the majority had good knowledge with a total of 75 respondents (60%) and the post-test results also the majority had good knowledge with a total of 114 respondents (91.2%), from the results of the pretest and posttest there was an increase in the level of knowledge due to the provision of leaflets as well as education on how to use and store eye drops.